2019
DOI: 10.1016/j.ejmech.2019.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Cell-active carbazole derivatives as inhibitors of the zika virus protease

Abstract: Zika virus (ZIKV) infection recently resulted in an international health emergency in the Americas in 2015-16 and despite its high profile there is still no approved treatment for ZIKV infection with millions of people being at risk. ZIKV is a member of Flaviviridae family which includes prominent members such as dengue virus (DENV) and West Nile virus (WNV). One of the best validated targets for developing anti-flaviviral treatment for DENV and WNV infection is the NS2B/NS3 protease.However the inhibitors rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Initial efforts were made to develop peptide-based protease inhibitors with or without a serine trap moiety such as CF 3 -ketone, an aldehyde, or a boronic acid that may mimic the substrate to resemble the substrate binding mode of the viral polyprotein to the viral protease and block its activity by forming a stabilized inhibitor-protease intermediate. However, peptides are, in general, unstable in vivo and mostly non-permeable to cross cell membranes, so focus has now shifted to the development of small molecules against flavivirus protease [ 63 ].…”
Section: Ns2b-ns3 Protease Inhibitorsmentioning
confidence: 99%
“…Initial efforts were made to develop peptide-based protease inhibitors with or without a serine trap moiety such as CF 3 -ketone, an aldehyde, or a boronic acid that may mimic the substrate to resemble the substrate binding mode of the viral polyprotein to the viral protease and block its activity by forming a stabilized inhibitor-protease intermediate. However, peptides are, in general, unstable in vivo and mostly non-permeable to cross cell membranes, so focus has now shifted to the development of small molecules against flavivirus protease [ 63 ].…”
Section: Ns2b-ns3 Protease Inhibitorsmentioning
confidence: 99%
“…Initial efforts were made to develop peptides-based protease inhibitor with or without serine trap. However, peptides are in general unstable in vivo and mostly non-permeable to cross cell membranes, so focus now has changed to develop small molecule against flavivirus protease [57].…”
Section: Synthetic Inhibitorsmentioning
confidence: 99%
“…Rassias et al synthesized a series of novel N-substituted carbazole-based amidines as ZIKV protease inhibitors, and compound 4 (carbazole derivative) demonstrated its in vitro biochemical and cell-based inhibitory profiles against ZIKV with an IC50 of 0.52 μM and EC50 of 1.25 μM [57]. Using quantitative high throughput screenings (qHTS) for small-molecule protease inhibitors, Abrams et al [58] found that compounds 5 (MK-591) and 6 (JNJ-40418677) showed antiviral effects primarily through inhibition of the Zika viral protease with IC50 values of 3.0 µM and 3.9 µM, respectively.…”
Section: Synthetic Inhibitorsmentioning
confidence: 99%
“…Several strategies, such as high throughput screening (HTS), computation-guided drug design, and fragment based drug discovery have been applied to develop protease in-hibitors [129][130][131][132][133]. The available inhibitors have been reviewed thoroughly [10,33,117,[134][135][136][137][138][139]. Inhibitors include substrate derived peptidic compounds, small molecules binding to the active site and allosteric inhibitors (Figure 5) [11].…”
Section: Protease Inhibitorsmentioning
confidence: 99%